2020
DOI: 10.3389/fspor.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Exercise Training on Adipose Tissue Mass, Glucose Uptake and Protein Content in Pre- and Post-menopausal Women

Abstract: The menopausal transition is accompanied by changes in adipose tissue storage, leading to an android body composition associated with increased risk of type 2 diabetes and cardiovascular disease in post-menopausal women. Estrogens probably affect local adipose tissue depots differently. We investigated how menopausal status and exercise training influence adipose tissue mass, adipose tissue insulin sensitivity and adipose tissue proteins associated with lipogenesis/lipolysis and mitochondrial function. Healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 47 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…One study was a non‐randomized controlled trial, 38 while another study utilized a controlled, repeated measures, longitudinal design 29 . The remaining 12 studies were neither randomized nor had a control group 26–28,39–47 . With regard to statistical power, only four out of 22 studies reported sample size calculations 32,33,37,40 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was a non‐randomized controlled trial, 38 while another study utilized a controlled, repeated measures, longitudinal design 29 . The remaining 12 studies were neither randomized nor had a control group 26–28,39–47 . With regard to statistical power, only four out of 22 studies reported sample size calculations 32,33,37,40 …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 12 studies were neither randomized nor had a control group 26–28,39–47 . With regard to statistical power, only four out of 22 studies reported sample size calculations 32,33,37,40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of glycolytic genes was significantly higher in postmenopausal as compared to premenopausal women in the present cohort. Studies performed by Mandrup et al suggest that there is a higher expression of hexokinase protein in abdominal adipose tissue as well as skeletal muscle tissue of postmenopausal women [ 36 ]. This may attribute to the estrogen production in adipose tissue; the key source of estrogen in post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%